THE NAMES OF ENGLISH JUDICIAL OFFICES, COURTS AND TRIBUNALS AND THEIR TRANSLATION INTO POLISH - GOŚCIŃSKI, Jan (Comparative Legilinguistics, 2016)
The aim of this article is to propose a number of translation techniques which can be applied in the process of translating the names of English judicial offices, courts and tribunals into Polish. In the first part, the author briefly describes the English court and tribunal system. In the second, he provides a theoretical background to the translation of legal terms. He devotes the third part to the techniques of translating the names of English courts and tribunals and the last one to the techniques of translating the names of English judicial offices. The article also has a practical aspect as it contains suggested Polish equivalents for the English names in question.